Modal Manusia Kewirausahaan dan Inovasi: Peran Kreativitas dalam Tinjauan Literatur Sistematis - Maliana Maliana; Yunia Wardi; Hendrik Heri Sandi (Siber Nusantara Publisher, 2026)
This study aims to systematically investigate the role of entrepreneurial human capital in fostering creativity and innovation in the context of entrepreneurship. The approach used is a systematic literature review (SLR) with reference to the PRISMA guidelines to identify, select, and synthesize relevant articles from reputable databases. The results demonstrate that entrepreneurial human capital, encompassing knowledge, skills, and experience, has a significant influence on increasing innovation capacity. Additionally, creativity plays a crucial role in the link between human capital and innovation through the ability to generate new ideas. The findings also indicate that the relationship between human capital and innovation is influenced by mediating variables such as absorptive capacity and moderating variables such as entrepreneurial orientation and the digital context. However, there are variations in the findings, indicating that the relationship between variables is complex and is influenced by contextual factors such as the organizational environment and individual characteristics. This study makes a theoretical contribution by integrating various perspectives into the explanation of the relationship between human capital, creativity, and innovation. Moreover, this study also offers practical implications for the development of entrepreneurship by improving the quality of human capital and creating an environment that supports innovation. Consequently, this study is expected to serve as a basis for further research in the field of innovation-driven entrepreneurship.